Zernike coefficients of digital holographic optical elements. - Son, J.-Y.,Venkel, T., Kim, J., Rodriguez-Ramos, J.M., Marichal-Hernandez, J.G. (Proceedings of SPIE - The International Society for Optical Engineering, 2024)
ABSTRACT The optical characteristics of digitally recorded holographic optical elements by the wavefront recording method are measured with a Shack-Hartmann wavefront sensor and their performances as an optical element are compared with those of a spherical mirror and an analog holographic optical element with use of the reconstructed wavefront by Zernike polynomial. The comparison shows that the digitally recorded holographic optical elements can work as a spherical mirror/lens, but it introduces wavefront aberration much more than the mirror and the analog holographic optical element.
Keywords: Digitally recorded holographic optical element, optical characteristics, Shack-Hartmann wavefront sensor, the reconstructed wavefront by Zernike polynomial, wavefront aberration